Student Digital Literacy Competence Study Language and Literature Education Program Indonesia - Panggabean, Sarma; Br. Saragih, Renita; Marulitua Sitorus, Male Onedy; Uli Lubis, Debora (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the digital literacy competence of Indonesian Language and Literature Education Study Program students. This study used a descriptive qualitative method to process the data from the sixth-semester student at HKBP Nommensen University. The results of this study found that students had good basic skills, major skills, intermediate skills, advanced skills, and literacy skills. However, the technical capabilities are still relatively poor. In (1) Basic Competencies, some problems are resolved properly, there are also several topical problems that still exist but at least there is an overview of problem-solving. (2) Students’ Basic Competencies have a fairly good introduction to the basics of computer equipment. (3) Students’ Intermediate Competencies increase at this stage, namely understanding various features on laptops, using printers, and using Ms. applications. Word and use of e-mail applications. The mastery of this competency is due to the fact that informants often carry out these activities so that they are more accustomed to their use. (4) Advanced Competencies to access information using search engines and online databases are good. (5) Technical Competencies of the Indonesian Language and Literature Study Program students as research informants do not yet have technical expertise regarding hardware and software. Informants have not been able to repair damage to digital equipment even at a simple level. (6) Students’ Digital Literacy Proficiency does not yet have sufficient literacy skills starting from formulating a search plan, establishing a search strategy, organizing, processing, applying and communicating information, and understanding standard citation formats, and do not have the effort to communicate information with technology.